Elevation of serum neurofilament light-chain levels disclose possible occult progressive multifocal leukoencephalopathy and immune reconstitution syndrome in a patient receiving ozanimod: a case report - Quintanilla-Bordás, Carlos; Gorriz, David; Cubas-Núñez, Laura; Castillo-Villalba, Jéssica; Carreres-Polo, Joan; Casanova, Bonaventura; Pérez-Miralles, Francisco Carlos (Frontiers in Immunology, 2024)
Background: We report the first case of findings suggestive of progressive multifocal leukoencephalopathy and immune restitution syndrome (PML-IRIS) in a patient with multiple sclerosis receiving ozanimod preceded by an unexpected increase in the serum neurofilament light chain (sNfL) levels.Case report: A 57-year-old-woman treated with ozanimod for the last eight years presented during surveillance MRI with findings compatible with PML-IRIS. Overt clinical symptoms were absent. sNfL levels increased 4 months earlier and peaked at presentation. Lymphocyte count nadired at 330 /mL 8 months earlier.The case illustrates the utility of sNfL levels for PML surveillance in patients receiving immunosuppressors.